2014
DOI: 10.1007/978-3-319-13817-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Weak Labels for Emotion Recognition of Tweets

Abstract: Abstract.Research on emotion recognition of tweets focuses on feature engineering or algorithm design, while dataset labels are barely questioned. Datasets of tweets are often labelled manually or via crowdsourcing, which results in strong labels. These methods are time intensive and can be expensive. Alternatively, tweet hashtags can be used as free, inexpensive weak labels. This paper investigates the impact of using weak labels compared to strong labels. The study uses two label sets for a corpus of tweets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In this line, researchers use sentimental hashtags and emoticons to label tweets as positive or negative. Mohammad [43] conducted two experiments which showed that the hashtag-based labels were consistent with the human annotations [7], and Janssens et al [45] compared valence of hashtag labels and human labels and indicated a high degree of agreement between them. Based on the previous research works, we used #happy, #excellent, #happiness, #sadness, #sad and #frustrated to collect target tweets using the Twitter official application programming interface (API) in 14 April 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, researchers use sentimental hashtags and emoticons to label tweets as positive or negative. Mohammad [43] conducted two experiments which showed that the hashtag-based labels were consistent with the human annotations [7], and Janssens et al [45] compared valence of hashtag labels and human labels and indicated a high degree of agreement between them. Based on the previous research works, we used #happy, #excellent, #happiness, #sadness, #sad and #frustrated to collect target tweets using the Twitter official application programming interface (API) in 14 April 2019.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Twitter is the main social media data source for sentiment analysis [4] and context-aware sentiment analysis [8]. For annotating data, we use a popular annotation approach for Twitter sentiment analysis called distant supervision [9,25,[43][44][45][46], also known as indirect crowdsourcing [7]. In this line, researchers use sentimental hashtags and emoticons to label tweets as positive or negative.…”
Section: Data and Experimental Setupmentioning
confidence: 99%